2012
DOI: 10.3109/19396368.2012.710869
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation status in patients with necrozoospermia

Abstract: The aim of this study was to determine if a relationship exists between the levels of sperm DNA fragmentation and necrospermia in infertile men. Semen samples obtained from 70 men consulting for infertility evaluation were analyzed according to World Health Organization (WHO) guidelines. Patients were subdivided into three groups according to the percentage of necrotic spermatozoa: normozoospermia (<30%; n = 20), moderate necrozoospermia (50-80%; n = 30), and severe necrozoospermia (>80%; n = 20). DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…In agreement with this finding, Samplaski et al [27] concluded that DFI testing may not be necessary in men with high (≥75%) and low (≤30%) levels of sperm vitality. In addition, our results support the results of Brahem et al [24], who found high levels of sperm DNA fragmentation in patients with necrozoospermia, a condition in which the proportion of non-viable spermatozoa in the ejaculate is increased significantly to more than 42%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with this finding, Samplaski et al [27] concluded that DFI testing may not be necessary in men with high (≥75%) and low (≤30%) levels of sperm vitality. In addition, our results support the results of Brahem et al [24], who found high levels of sperm DNA fragmentation in patients with necrozoospermia, a condition in which the proportion of non-viable spermatozoa in the ejaculate is increased significantly to more than 42%.…”
Section: Discussionsupporting
confidence: 92%
“…Sperm vitality and progressive motility exhibited the most significant associations, which could be explained by the significant role of epididymal function in sperm pathology. Due to long exposure to overproduced reactive oxygen species (ROS) at epididymal level by both leukocytic and nonleukocytic cells, such as immature spermatozoa [20], epididymal epithelial cells [21] and spermiophages [22], ROS-induced sperm membrane peroxidation results in loss of sperm motility, membrane integrity, and consequently, loss of sperm vitality [23][24][25]. Moreover, ROS capable of penetrating sperm membrane can impair sperm DNA integrity either directly by attacking DNA backbone and by forming abasic sites and DNA adducts or indirectly by triggering the apoptotic cascade through the activation of caspases and endonucleases [26].…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between sperm concentration and SDF in subfertile men appears to vary, a correlation between SDF and sperm viability has been demonstrated [15]. Although the mechanisms have not been fully recognized, SDF is seen in mature, viable sperm.…”
Section: Introductionmentioning
confidence: 99%
“…DNA breaks are among primary factors inducing spermatozoa apoptosis (12,31). The literature has demonstrated a clear link between DNA fragmentation and sperm viability (6).…”
Section: Resultsmentioning
confidence: 99%